Unpacking the cost implications of diagnosis-related groups reform for lumbar disc herniation patients in Chinese medicine: a closer look at evidence from China - Chen, Meng-en; Wang, Yu-han; Yu, Jing; Xia, Shi-ji; Zhang, Xiao-xi; Wang, Yan; Yuan, You-shu; Jia, Xuan; Sun, He-nong; Wu, Guo-ping; Wang, Jia-yi; Cong, Tian-zhen; et al. (Frontiers in Public Health, 2025)
ObjectivesLumbar disc herniation (LDH) presents a significant economic burden globally, worsening in China due to an aging population. Traditional Chinese Medicine (TCM) offers effective treatment options for LDH, making its integration with Diagnosis-Related Groups (DRG) payment reform crucial for reducing medical costs and enhancing healthcare quality.MethodsWe analyzed data from hospitalized patients at Qingyang City Hospital of Chinese Medicine, Gansu Province, from 2017 to 2022. Univariate analysis was conducted to examine changes in patient demographics before and after the DRG reform. A single group interrupted-time series analysis (ITSA) model was used to compare key indicators of medical costs and length of stay pre- and post-reform.ResultsA total of 2,857 LDH patients were included in the study. Pre-DRG reform, 1,294 patients were recorded, with males comprising 46.06% and a mean age (SD) of 58.29 (14.22) years. Post-DRG reform, 1,563 patients were observed, with males accounting for 40.88% and a mean age (SD) of 60.64 (14.25) years. No significant differences were found in nationality, marital status, use of Chinese medicine diagnostic and therapeutic equipment, use of Chinese medicine diagnostic and treatment techniques or diagnosis and treatment based on Chinese medicine evidence (p > 0.05). However, significant differences were noted in sex, age, visit times, admission pathways, admission disease status, complications and comorbidities, and surgeries and operations (p < 0.05). Healthcare-related costs and length of stay are associated with sex, age, visit times, and other factors, showing a positive correlation among different costs and length of stay (p < 0.05). Post-reform, average monthly hospitalization cost decreased by CNY 36.78 (β1+β3=−36.78,p < 0.05), Chinese medicine cost fell by CNY 8.87 (β1+β3=−8.87,p < 0.05), and Western medicine cost dropped by CNY 31.68 (β1+β3=−31.68,p < 0.05). While the rising trend in diagnosis cost was curtailed, both medical services cost and TCM treatment cost increased, with the length of stay remaining stable.ConclusionThe DRG reform is associated with lower hospitalization cost and reduced costs for both Chinese medicine and Western medicine. However, its impact on overall medical services cost, diagnosis cost, TCM treatment cost, and length of stay is limited. Future DRG reform should leverage the distinctive advantages of TCM, enhance the payment system, improve treatment outcomes, and further reduce healthcare costs while shortening hospitalization times.